Influence of 11 ginsenoside monomers on action potentials of myocardiocytes - Y Jiang; L Chen; CW Sun; GG Zhong; H Qi; XY Ma; JD Xu (Acta Pharmacologica Sinica, 2017)
Influence of 11 ginsenoside monomers on action potentials of myocardiocytes